(untitled) (Malaysian Management Journal, 2022)
This study examines the impact of the National Economic Empowerment and Development Strategy (NEEDS) programme on poverty reduction in Sokoto State of North-western Nigeria, through the channels of the education policy. A total of 826 responses from 11 Local Government Areas (LGAs) were received through a structured questionnaire. The data was analysed using descriptive statistics and the binary logit regression model. It is found that the NEEDS has had a significant impact on the education of the participating households, which could lead to poverty reduction in the study area. The results also reveal that the NEEDS educational policy is likely to empower the youth to be self-reliant and productive in order to combat poverty in Sokoto State. It is suggested that the government should plan educational policies in the context of poverty reduction, by creating a conducive atmosphere for learning. Further, those who have benefited from similar programmes can be involved in raising awareness of future programmes. In addition, the government should enact a law on children’s education so that domestic work in the household and family businesses do not interfere with children’s education.